Methodological and Practical Considerations in Rapid Qualitative Research: Lessons Learned From a Team-Based Global Study During COVID-19 Pandemic. (27th August 2021) - Luciani, Michela; Strachan, Patricia H.; Conti, Alessio; Schwartz, Lisa; Kapiriri, Lydia; Oliphant, Allyson; Nouvet, Elysée
Rapid qualitative research (RQR) studies are increasingly employed to inform decision-making in public health emergencies. Despite this trend, there remains a lack of clarity around what these studies actually involve in terms of methodological processes and practical considerations or challenges. Our team conducted a global RQR study during the COVID-19 pandemic. In this article, we provide a detailed account of our methodological processes and decisions taken related to ethics, study design, and analysis. We describe how we navigated limitations on time and resources. We draw attention to several elements that operated as facilitators to the rapid launch and completion of this study. Rendering methodological considerations and rationales for specific RQR studies explicit and available for consideration by others can contribute to the validity of RQR, support further discussion and development of RQR methods, and make findings for particular studies more credible.